ESRC-DFID Research for policy and practice: water security - Bioversity International (Impact Initiative, 2019)
Access to clean water is essential for life and yet 80 per cent of the world’s population live in areas threatened by waterinsecurity. All too often in water management, short-term gains for the few are prioritised above long-term benefits for the many. This must stop, if we are to deliver on Sustainable Development Goal 6: ensure availability and ustainable management of water and sanitation for all. Over-allocation, pollution, extreme weather, urbanisation, land degradation, and conflict can all conspire against progress to achieve water security for all. Weak water overnance undermines health, livelihoods, and economic opportunity, and consistently, vulnerable people and communities feel the brunt of these impacts. To effectively address the global water crisis, and the crushing inequalities it reinforces around the world, we need reliable and objective evidence about what is happening. It is essential that we do not isolate water as an issue, and work together with researchers, governments, businesses, and community groups. It is only then that we can access the knowledge needed to forge durable solutions. The selection of Economic and Social Research Council (ESRC) and Department for International Development (DFID)-funded research that follows, explores the realities facing people for whom water insecurity is a daily threat. Experiences of managing reservoirs in Burkina Faso identifies the challenges and conflicts facing user groups. Meanwhile, in Ethiopia, a study of pastoralists looks at the inter-relationships between emotional wellbeing and water access. This small snapshot provides useful insights for what is needed to tackle the global water crisis. Central to both projects are collaborative ways of working and iterative dialogues between research and policy communities, water users, and citizens. Working in this way is key to understanding the complexities and discovering new solutions to tackling the world’s spiralling water resource challenges.